2014
DOI: 10.1016/j.cllc.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Dihydropyrimidine Dehydrogenase in Lung Adenocarcinoma is Associated With Mutations in Epidermal Growth Factor Receptor: Implications for the Treatment of Non–Small-Cell Lung Cancer Using 5-Fluorouracil

Abstract: Running title: DPD and EGFR mutation in adenocarcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The difference in PFS was not statistically significant [HR 0.78; 95 % confidence interval (CI) 0.57-1.06; p = 0.11]. In the First-SIGNAL trial, similar ORRs were reported in patients with and without EGFR mutations who were treated with cisplatin-gemcitabine (38 vs. 52 %, Tumors positive for EGFR mutations has a higher incidence of DPD immunopositivity (p = 0.003) Mochinaga et al (2014) respectively; p = 0.36). The PFS of the two subgroups was the same (6.3 vs. 6.4 months, respectively; HR 0.679; 95 % CI 0.34-1.35; p = 0.27).…”
Section: Predictive Roles Of Egfr Mutations In Response To Cytotoxic supporting
confidence: 78%
See 2 more Smart Citations
“…The difference in PFS was not statistically significant [HR 0.78; 95 % confidence interval (CI) 0.57-1.06; p = 0.11]. In the First-SIGNAL trial, similar ORRs were reported in patients with and without EGFR mutations who were treated with cisplatin-gemcitabine (38 vs. 52 %, Tumors positive for EGFR mutations has a higher incidence of DPD immunopositivity (p = 0.003) Mochinaga et al (2014) respectively; p = 0.36). The PFS of the two subgroups was the same (6.3 vs. 6.4 months, respectively; HR 0.679; 95 % CI 0.34-1.35; p = 0.27).…”
Section: Predictive Roles Of Egfr Mutations In Response To Cytotoxic supporting
confidence: 78%
“…Although the findings of basic research also support this observation (Mochinaga et al 2014;Suehisa et al 2007), there is not enough evidence supporting the avoidance of adjuvant 5-FU-based agents in the treatment for lung cancers with EGFR mutations in clinical practices.…”
Section: Subset Analyses (Egfr-mutation-positive) Of Patients Selectementioning
confidence: 73%
See 1 more Smart Citation
“…The TS expression level was low in patients with well-differentiated NSCLC; DPD was downregulated in patients with squamous cell carcinoma, which was negatively correlated with maximum tumor diameter; TP was highly expressed in patients with vascular invasion; and the OPRT level was decreased in patients with adenocarcinoma. The reason for these findings is not known; however, it was reported that adenocarcinoma in situ, previously classified as bronchioloalveolar carcinoma (16), has a significantly higher epidermal growth factor receptor (EGFR) mutation frequency and DPD mRNA levels compared with other histological types (17), which may explain the high DPD mRNA levels observed in adenocarcinoma. On the other hand, OPRT activity is known to be increased in rapidly growing cells, including normal cells, such as those in the testis (18).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the rs2293347GA/AA genotype was associated with a lower risk of progressive disease compared with the rs2293347GG genotype (OR = 0.048, p = 6.32 × 10 −5 ). Recently, Mochinaga et al reported that high expression of DPD in lung adenocarcinoma is associated with mutations in EGFR [ 44 ]. Several studies have demonstrated that high DPD levels result in low sensitivity to fluoropyrimidine for various cancers, such as gastric cancer [ 45 , 46 ], colon cancer [ 47 ], bladder cancer [ 48 ], and breast cancer [ 49 ].…”
Section: Discussionmentioning
confidence: 99%